From voting to engaging: promoting democratic values across an international school network. (2nd November 2018) - Higham, Rupert; Djohari, Natalie
Abstract: Using a mixed methods design, the researchers investigated understandings and practices of democracy across Round Square, a worldwide network of 180 schools committed to shared values. An extensive questionnaire received 4020 student and 863 teacher returns; additionally, leaders, students, and parents from five case study schools on different continents were interviewed. All stakeholder groups were found to value democracy highly, but saw its implementation in their schools as challenging and limited. While staff and parents espoused more holistic understandings of democratic practices and cultures, students focused primarily on systems of election and representation. A philosophically informed framework for developing 'responsible leadership', and a values-led approach to school improvement, are offered to deepen students' democratic agency through informed, active, and reflective engagement with people, situations, and curricula.